Intrapericardial Liver Herniation Associated with Massive Pericardial Effusion and Horseshoe Kidney Anomaly - Senaylı, Atilla; Demirtürk, Fazlı; Çalışkan, Ahmet; Elalmış, Altay; Bıçakçı, Ünal; Aytan, Hakan (Gynecology Obstetrics & Reproductive Medicine, 2006)
A rare type of diaphragm herniation, intrapericardial liver herniation associated with massive pericardial effusion and horseshoe kidney anomaly is reported. A 24-ears-old, primigravid woman with 32 weeks of gestation was admitted for the first time for control. Congenital diaphragmatic hernia was diagnosed. Infant was operated after diagnostic work-up in the second week of her life. At thoracotomy herniation of the liver into the pericardium was observed. The defect was repaired with a polypropylene mesh; however, unfortunately patient died at the post operative 45th day. Intrapericardial liver herniation with pericardial effusion is a rare condition which is difficult to differentiate from some other thoracic cystic lesions. This kind of herniation must be kept in mind when an intrathoracic cystic lesion is evaluated.